The Urgency of Food Estate for National Food Security in The Middle of The COVID-19 Pandemic - Ahmad Nizami Fadillah; Sisgianto; Mohammad Jafar Loilatu (Mengeja Indonesia Publisher, 2021)
The Indonesian government developed the Food Estate program as one of the spearheads in a food security strategy during the COVID-19 pandemic. The Food Estate concept is a food development on a wide scale carried out in an integrated manner, including agriculture, plantations, and livestock in an area. This study uses descriptive and qualitative approaches to explain and analyze research problems. Data collection was obtained from the literature study regarding previous research and expert opinion. Overall, food estate development can increase per capita income and reduce the percentage of income for daily food needs, which is essentially very important if the government is to have more policy options in the event of a global food crisis due to COVID-19. However, there should be an improvement in the smooth distribution so that there is no longer a shortage of food, which impacts hoarding for consumer groups, causing shortages for other groups. The COVID-19 pandemic, of course, has taught the relationship between the health of the environmental system and the food system. Therefore, the synergy between food, ecological systems, and economic systems is an obligation.